VISITORS´ EXPERIENCES TOWARDS SUSTEINABILITY CHALLENGES IN ARCHAELOGICAL-HERITAGE SITES: A NETNOGRAPHIC STUDY ON ANCIENT CITY OF KNIDOS, TURKEY - MELTEM; Cafer Topaloglu (Enlightening Tourism: A Pathmaking Journal)
This study used netnography to explore the sustainability challenges in visitors’ reviews in Knidos archeological site, located on the southern coast of Mugla, Turkey, as expressed in user-generated content (UGC) on the TripAdvisor website. Data was obtained from visitors' narratives on their reviews posted on TripAdvisor. A total of 1076 narratives were accessed for all years. However, researchers retrieved 638 narratives posted in the last six years between 2016 and 2021 to reach up-to-date experiences. The data were thematically analyzed using the qualitative data analysis software MAXQDA for compiling and coding data, creating main and sub-themes, defining code frequencies, determining the relationships between codes, and creating code maps. The analysis revealed five main codes of heritage reviews: attractions, place perception, sustainability challenges, place attachment, and behavioral intention. The complex code configurations revealed that visitors had positive place perceptions, strong behavioral intentions, and high place attachment despite the site’s sustainability challenges. Furthermore, attractions, place attachment and place perception are the important antecedents of positive recommendation intention. The study makes a substantial contribution to the literature on sustainable development and visitors’ behavior by providing a deep understanding of the sustainability challenges and visitor experiences narrated about a specific archeological city through online user-generated content (UGC).